Identification of novel clinical subtypes in patients with microscopic polyangiitis using cluster analysis: multicenter REVEAL cohort study - Okazaki, Ayana; Matsuda, Shogo; Kotani, Takuya; Fukui, Keisuke; Gon, Takaho; Watanabe, Ryu; Manabe, Atsushi; Shoji, Mikihito; Kadoba, Keiichiro; Hiwa, Ryosuke; Yamamoto, Wataru; Hashimoto, Motomu; et al. (Frontiers in Immunology, 2025)
IntroductionThis study aimed to identify new clinical phenotypes of microscopic polyangiitis (MPA) using a principal components analysis (PCA)-based cluster analysis.MethodsA total of 189 patients with MPA between May 2005 and December 2021 were enrolled from a multicenter cohort in Japan (REVEAL cohort). Categorical PCA and cluster analysis were performed based on clinical, laboratory, and radiological findings. Clinical characteristics and outcomes, including all-cause mortality, respiratory-related mortality, end-stage renal disease (ESRD), and relapse were compared between each cluster.ResultsEleven clinical variables were transformed into four components using categorical PCA and synthetic variables were created. Additionally, a cluster analysis was performed using these variables to classify patients with MPA into subgroups. Four distinct clinical subgroups were identified: Cluster 1 included the renal involvements and diffuse alveolar hemorrhage (DAH)-dominant group (N=33). Cluster 2 comprised the elderly onset systemic inflammation group (N=75). Cluster 3 included patients in the younger-onset limited-organ disease group (N=45). Cluster 4 was comprised of an ILD-predominant group without kidney involvement (N=36). 61 patients died during follow-up, with 32 dying of respiratory-related causes. Additionally, 19 patients developed ESRD and 70 relapsed. Cluster 1 showed the worst ESRD-free survival and relapse rates, whereas Cluster 2 showed the worst overall survival and respiratory-related death-free survival rates among the four groups.ConclusionsOur study identified four unique subgroups with different MPA outcomes. Individualized treatments for each subgroup may be required to improve the prognosis of MPA.